Cascading effects of mammal host community composition on tick vector occurrence at the urban human–wildlife interface - Jonathan Bastard; Nichar Gregory; Pilar Fernandez; Michaela Mincone; Olivia Card; Meredith C. VanAcker; Sara Kross; Maria A. Diuk‐Wasser (Ecosphere)
Abstract Habitat fragmentation and host community composition are implicated as key drivers of changing tick populations and tick‐borne pathogen dynamics, altering infection risk through coupled socioecological pathways that mediate interactions between tick vectors, vertebrate hosts, and humans. Patterns of host diversity may be particularly idiosyncratic across urbanized landscapes, due to trade‐offs between extreme fragmentation that reduces habitat suitability and access, and human activities that artificially increase resource availability for wildlife. We used camera and hair trap surveys and tick sampling to identify links between landscape composition and configuration, the mammalian host community, and the presence of three tick vector species at a human–wildlife interface in New York City, an emerging area within an endemic region for several tick‐borne diseases. We found that human infrastructures, such as the presence of fences in yards, could affect mammal host community composition by changing the “hardness” of edges between urban greenspaces and residential areas. We identified yard‐ and broader landscape‐level features associated with the presence of urban mammal species, and identified cascading effects of host community composition on tick distribution in yards, suggesting management implications for the mitigation of human exposure to tick‐borne pathogens. In particular, we identified a possible role of ubiquitous mesomammals, such as raccoons (Procyon lotor), in transporting Amblyomma americanum ticks between parks and neighboring residential yards, and confirmed the key role of white‐tailed deer (Odocoileus virginianus) for introducing Ixodes scapularis ticks into yards. Our results challenge assumptions that biodiversity loss in human‐modified areas always increases the risk for tick‐borne diseases. Instead, we found many residential sites had higher mammal species richness and higher detection of low reservoir competent (“dilution”) hosts for Borrelia burgdorferi, such as opossums (Didelphis virginiana), than paired forested greenspaces. Our study highlights the importance of disentangling the mechanisms mediating tick‐borne disease hazard as a critical first step toward reducing urban tick‐borne disease risk.